2002
DOI: 10.1159/000065638
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Disorders of Executive Cognitive Functioning among the Elderly: Findings from the San Luis Valley Health and Aging Study

Abstract: The San Luis Valley Health and Aging Study is a population-based epidemiologic study of chronic illness and disability among Hispanic and non-Hispanic white persons over the age of 60 in two counties in rural southern Colorado, USA. Between 1993 and 1995, we examined the prevalence of impaired executive cognitive functioning in a sample of 1,313 individuals living both in the community and in nursing homes. Overall, 1 person in 3 was found to have at least mild impairment, while 1 in 6 had moderate to severe d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
19
0
2

Year Published

2002
2002
2015
2015

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 31 publications
(56 reference statements)
5
19
0
2
Order By: Relevance
“…Moreover, an equally large fraction may have isolated ECF impairment and escape detection. This is consistent with the high frequency of ECF impairment in community samples [25,35] and represents an essentially unadressed cause of disabling cognitive impairment.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Moreover, an equally large fraction may have isolated ECF impairment and escape detection. This is consistent with the high frequency of ECF impairment in community samples [25,35] and represents an essentially unadressed cause of disabling cognitive impairment.…”
Section: Discussionsupporting
confidence: 85%
“…At baseline, 38% of the FHS sample failed these measures at these thresholds [10]. This is similar to the only published population-based prevalence study of ECF impairment in community-dwelling elderly persons (i.e., 33.3%) [25].…”
Section: Discussionsupporting
confidence: 80%
“…Behavioral Self-Regulation: The primary measure of ECF used in the study was the Behavioral Dyscontrol Scale (BDS; Grigsby, Kaye, & Robbins, 1992;Kaye, Grigsby, Robbins, & Korzun, 1990), an extensively-validated measure of the capacity for behavioral self-regulation involving intentional control of simple voluntary motor behavior (Diesfeldt, 2004;Ecklund-Johnson, Miller, & Sweet, 2004;Grigsby et al, 2002b;Grigsby, Kaye, Baxter, Shetterly, & Hamman, 1998;Grigsby, Kaye, Eilertsen, & Kramer, 2000;Grigsby et al, 1992;Kaye et al, 1990). Based on the work of Luria (1966Luria ( , 1980 and Fuster (1997Fuster ( , 2000, the BDS was developed to measure the capacity to use intentions to guide the performance of goal-directed, purposeful activity.…”
Section: Methodsmentioning
confidence: 99%
“…While some authors find education to be a variable that affects the age-related decline in executive functioning, with low education exacerbating age effects and high education associated with more successful aging, (Van der Elst et al 2006;Grigsby et al 2002), others find education to be a poor predictor of executive performance (Manly et al 2005;Hashimoto et al 2006). Plumet et al (2005) utilized a sorting task (MCST) and found that distractive errors were exhibited at the same rate in participants over the age of 70, regardless of level of education attained.…”
Section: Executive Functions In the Aging Populationmentioning
confidence: 99%